Changing patterns of variability in cereal prices and production - Hazell, Peter B. R. (International Food Policy Research Institute, 1988)
The substantial growth in world cereal production of the past two and onehalf decades has been accompanied by a widening band of variability around the trend. Although each trough in production has been consistently higher than in all previous downturns, the probability that aggregate production can fall substantially below trend has increased since the 1960s.